ANALISIS PENGGUNAAN PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP PROFITABILITAS DI BANK UMUM SYARIAH PERIODE 2015-2018 - Heikal Muhammad Zakaria; Gusganda Suria Manda; Arif Rakhman (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
This study is aiming to determine the effect of mudharabah financing on the profitability (ROA) in Sharia Commercial Banks (BUS) for the 2015-2018 period, the effect of musyarakah financing on the profitability (ROA) on Sharia Commercial Banks (BUS) for the 2015-2018 period, and the effect of mudharabah and musyarakah financing on the profitability (ROA) in Sharia Commercial Banks (BUS) for the 2015-2018 period. This research is a type of associative research with a quantitative approach. This study uses secondary data with the period of 2015-2018 observation. The data used is sourced from the Sharia Banking (SPS) and the Sharia Bank's annual financial statements from 2015 to 2018. The analysis used is multiple linear regression analysis. Data is processed using SPSS version 16. The results of the study show that mudharabah financing has a significant positive effect on the profitability (ROA) of Sharia Commercial Banks (BUS) for the 2015-2018 period. Musyarakah financing has a significant negative effect on profitability (ROA) of Sharia Commercial Banks (BUS) for the 2015-2018 period. Mudharabah financing and musyarakah financing have a positive significant effect on the profitability (ROA) of Sharia Commercial Banks (BUS) for the 2015-2018 period.